2012
DOI: 10.1371/journal.pone.0046122
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Changes in Corticospinal Excitability during Voluntary Contraction with Concurrent Electrical Stimulation

Abstract: While previous studies have assessed changes in corticospinal excitability following voluntary contraction coupled with electrical stimulation (ES), we sought to examine, for the first time in the field, real-time changes in corticospinal excitability. We monitored motor evoked potentials (MEPs) elicited by transcranial magnetic stimulation and recorded the MEPs using a mechanomyogram, which is less susceptible to electrical artifacts. We assessed the MEPs at each level of muscle contraction of wrist flexion (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…The combination of the activities of the somatosensory afferents and intrinsic motor cortical circuits may be important for inducing cortical plasticity (Stefan et al, 2000). It is known that MI alone and ES alone (Bakker et al, 2008; Yamaguchi et al, 2012), and MI using electroencephalography combined with ES (Mrachacz-Kersting et al, 2012) increase the excitability of a region of the primary motor cortex in real time. It is possible that the spike-timing-dependent plasticity resulting from combined inputs may have occurred at a synapse somewhere in corticospinal pathway of the TA (Stefan et al, 2000; Stinear and Hornby, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of the activities of the somatosensory afferents and intrinsic motor cortical circuits may be important for inducing cortical plasticity (Stefan et al, 2000). It is known that MI alone and ES alone (Bakker et al, 2008; Yamaguchi et al, 2012), and MI using electroencephalography combined with ES (Mrachacz-Kersting et al, 2012) increase the excitability of a region of the primary motor cortex in real time. It is possible that the spike-timing-dependent plasticity resulting from combined inputs may have occurred at a synapse somewhere in corticospinal pathway of the TA (Stefan et al, 2000; Stinear and Hornby, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…ES was delivered with a frequency of 100 Hz (pulse width 1 ms) for 2 s at an intensity of 120% of the sensory threshold of the TA at rest without muscle contraction. This stimulus intensity was determined so that MEP can be increased to a level greater than those at rest when combined with MI (Yamaguchi et al, 2012). A trial consisted of stimulation for 2 s and a rest period of 4 s. 200 trials were conducted over 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…This LTD-like response may be specific to horizontal cortical connections strengthened by enhanced activity of proprioceptive afferents during the active motor contraction maintained under the PAS ACTIVE condition. Previous studies have reported that peripheral nerve stimulation coupled with volitional contraction of muscles innervated by the stimulated nerve produced changes in corticomotor excitability to that muscle (Khaslavskaia and Sinkjaer, 2005; Yamaguchi et al, 2012) and increased the sensitivity between neural projections of the contralateral S1 and M1 (Gandolla et al, 2014). However, interactions between the peripheral nerve stimulation, volitional muscle contraction and motor cortical stimulation all likely contributed to differences in SICI following PAS ACTIVE as no such modulations were observed with peripheral nerve stimulation and volitional muscle contraction alone during the PAS CONTROL condition.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it was shown that delivery of electrical stimulation at the onset of muscle electromyographic (EMG) activity during wrist extension was successful in facilitating corticospinal MEP responses, while electrical stimulation alone was not [ 142 ]. Voluntary activations and electrical stimulation can also induce reciprocal changes in corticospinal excitability in agonist and antagonist muscles [ 155 ]. Using fMRI, the magnitude of cortical activation changes relative to rest were shown to be larger during voluntary contractions of upper-limb muscles compared to FES-induced movements in the M1, S1, and SMA areas [ 57 ].…”
Section: Brain-controlled Electrical Stimulation Of Muscles and Nervementioning
confidence: 99%